Lexical variation of somatic verbal idioms in Colombian Spanish: diatopic and diaphasic variation, and polysemy (Islas, 2024)
Introduction: This article presents the final results of a study on the lexical variation of somatic verbal idioms related to the human and animal body, as used in Colombia and Spain.Methods: Computational tools —linguistic corpora and multilingual databases— were incorporated into the study of phraseological variation in Spanish to overcome the limitations of relying solely on dictionaries.Results: The somatic verbal idioms of Colombian Spanish can present somatic, anthropomorphic and/or zoomorphic variants. According to the frequency of appearance of somatic lexemes in our database, the most productive body parts in Colombian phraseology are those related to the head (46%), the trunk (21%), the extremities (19%), body fluids (7%), skin (5%) and others (2%).Conclusions: The primary intention behind the lexical variation of somatic (somatic and anthropomorphic) verbal idioms in Colombian Spanish is to create a pragmatic effect (euphemistic, dysphemistic, or humorous), while the secondary intention is to animalize individuals (zoomorphic).
Keywords: dialectal phraseology; somatism; anthropomorphism; zoomorphism; Colombian Spanish